Book acquisition preferences among Rio de Janeiro municipal teachers - Beltrao, Kaizo Iwakami; Duchiade, Milena Piraccini (Education Policy Analysis Archives, 2017)
Teacher quality is an important factor in education enhancement, and it is strongly related to student achievement. Reading is a good cultural indicator of a population and a tool for one´s self-improvement. International studies concluded that teachers, the would-be role model for students, are seldom avid readers. Recently, many Brazilian state programs have been implemented aiming at encouraging reading habits, but they are seldom evaluated. Since 2001, Rio de Janeiro City Department of Education (RJCDE) distributes annually to elementary and secondary teachers a voucher exchangeable for any book of their choice. We analyzed books chosen by almost 26,000 teachers in 2012. The tally of the books showed a large variety of titles. Literature was the most prominent group, followed by Children’s and Adolescent Literature, which indicates a possible acquisition for family members. Almost one-fifth of the titles were scientific, technical or professional books, which shows a desire for personal and/or professional self-improvement. Teachers from the primary grades presented a distinct set of preferences from secondary grade teachers. The reading habit, as aesthetic pleasure, entertainment, self-improvement, or family reading, requires freedom of choice. The RJCDE program treats teachers as independent adults, responsible for their own choices.